Austenitic stainless steel alloy material
By adjusting the chemical composition of the austenitic stainless steel alloy material and pre-existing precipitates, the problem of stress relaxation cracks in boiler use is solved, the excellent creep strength and stress relaxation crack resistance of the material are achieved, and the high temperature environment is ensured. Stability and durability.
Patent Information
- Application Number
- CN202380044299.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-06-06
- Publication Date
- 2025-01-10
AI Technical Summary
The austenitic stainless steel alloy materials used in boilers are prone to stress relaxation cracks in high temperature environments. The existing technology has not effectively solved this problem and has failed to take into account excellent creep strength and stress relaxation crack resistance.
By adjusting the chemical composition, it includes elements such as C: 0.03 to 0.12%, Si: 0.05 to 2.00%, Mn: 0.05 to 3.00%, Ni: 18.0% or more and less than 25.0%, Cr: 22.0% or more and less than 30.0%, and In the material, there are 5,000 precipitates of 0.5 to 2.0 μm diameters of 5,000 precipitates of 0.5 to 2.0 μm diameters in advance, so as to increase the grain boundary area to improve stress relaxation crack resistance.
The excellent creep strength and stress relaxation and crack resistance of the material under high temperature environment are achieved, ensuring the stability and durability of the material after welding and bending processing.
Smart Images

Figure BDA0005163877150000231 
Figure BDA0005163877150000241 
Figure BDA0005163877150000251
Abstract
Description
Technical Field
[0001] The present disclosure relates to alloy materials, and more particularly to austenitic stainless steel alloy materials. Background Art
[0002] Austenitic stainless steel alloy materials are used as materials for boiler applications such as coal-fired boilers, biomass boilers, and HRSG (Heat Recovery Steam Generator). Materials used for these boiler applications are required to have excellent creep strength in a high temperature environment.
[0003] Austenitic stainless steel alloy materials with improved creep strength are proposed in International Publication No. 2009 / 044796 (Patent Document 1) and Japanese Patent Application Laid-Open No. 2004-250783 (Patent Document 2).
[0004] The austenitic stainless steel alloy material disclosed in Patent Document 1 contains C: 0.04-0.18%, Si: 1.5% or less, Mn: 2.0% or less, Ni: 6-30%, Cr: 15-30%, N: 0.03-0.35%, and sol.Al: 0.03% or less, and contains one or more elements of Nb: 1.0% or less, V: 0.5% or less, and Ti: 0.5% or less, and the balance is Fe and impurities. In this alloy material, P1 (=S+{(P+Sn) / 2}+{(As+Zn+Pb+Sb) / 5}) is also 0.06 or less, and P2 (=Nb+2(V+Ti)) is also 0.2-1.7-10×P1. In the alloy material disclosed in this document, by setting P2, which is an index of Nb, V, and Ti, to 0.2 or more, precipitates are generated when used in a high-temperature environment, thereby improving creep strength.
[0005] The austenitic stainless steel alloy material disclosed in Patent Document 2 contains, by mass%, C: 0.03-0.12%, Si: 0.2-2%, Mn: 0.1-3%, P: 0.03% or less, S: 0.01% or less, Ni: more than 18% and less than 25%, Cr: more than 22% and less than 30%, Co: 0.04-0.8%, Ti: more than 0.002% and less than 0.01%, Nb: 0.1-1%, V: 0.01-1%, B: more than 0.0005% and less than 0.2%, sol.Al: more than 0.0005% and less than 0.03%, N: 0.1-0.35%, and O (oxygen): 0.001-0.008%, with the remainder being Fe and impurities. In the alloy material disclosed in this document, Ti, Nb, and V are contained, so that precipitates are generated when used in a high-temperature environment, thereby improving creep strength.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2009 / 044796
[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-250783 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, austenitic stainless steel alloy materials for boilers are welded or bent when used in boilers. Austenitic stainless steel alloy materials used in boilers are used in high temperature areas of 500 to 750°C for a long time. At this time, residual stress relaxation occurs in the welded parts of the austenitic stainless steel alloy materials and the parts subjected to bending. Due to the relaxation of residual stress, precipitates are generated in the grains, causing hardening in the grains. Therefore, creep strain accumulates at the grain boundaries, and cracks sometimes occur at the grain boundaries. Such cracks are called stress relaxation cracks.
[0012] Austenitic stainless steel alloy materials for boiler applications require not only excellent creep strength but also excellent stress relaxation cracking resistance. In the above patent documents, although research related to creep strength is conducted, research related to stress relaxation cracking resistance is not conducted.
[0013] An object of the present disclosure is to provide an austenitic stainless steel alloy material having excellent creep strength and excellent stress relaxation cracking resistance.
[0014] Solutions for solving problems
[0015] The austenitic stainless steel alloy material disclosed herein contains, by mass%,
[0016] C: 0.03~0.12%,
[0017] Si: 0.05-2.00%,
[0018] Mn: 0.05-3.00%,
[0019] P: 0.03% or less,
[0020] S: 0.010% or less,
[0021] Ni: 18.0% or more and less than 25.0%,
[0022] Cr: 22.0% or more and less than 30.0%,
[0023] Co: 0.04-0.80%,
[0024] Ti: 0.002~0.010%,
[0025] Nb: 0.1-1.0%,
[0026] V: 0.01~1.00%,
[0027] Al: 0.001% or more and less than 0.030%,
[0028] N: 0.10~0.35%,
[0029] Mo: 0-1.00%,
[0030] W: 0~1.00%,
[0031] B: 0~0.010%, and
[0032] Ca: 0 to 0.0100%, and
[0033] The balance is Fe and impurities.
[0034] The number density of precipitates with a circle equivalent diameter of 0.5 to 2.0 μm in the austenitic stainless steel alloy material is 5000 / mm 2 above.
[0035] Effects of the Invention
[0036] The austenitic stainless steel alloy material disclosed in the present invention has excellent creep strength and excellent stress relaxation crack resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a perspective view of a C-ring type restrained weld crack test piece used in a stress relaxation crack resistance evaluation test.
[0038] Figure 2 It is used to illustrate the use of Figure 1 Schematic diagram of the method of evaluating the stress relaxation cracking resistance of the C-ring type restrained weld crack test piece shown.
[0039] Figure 3 This is an enlarged view of the vicinity of the notch bottom in the cross section perpendicular to the pipe axis direction of the C-ring type restraint weld crack test piece in the stress relaxation crack resistance evaluation test in the examples. DETAILED DESCRIPTION
[0040] The present inventors have studied austenitic stainless steel alloy materials that can achieve both excellent creep strength and excellent stress relaxation crack resistance. First, the present inventors tried to achieve both excellent creep strength and excellent stress relaxation crack resistance from the perspective of chemical composition. As a result, it is believed that if the chemical composition is as follows, it is possible to achieve both excellent creep strength and excellent stress relaxation crack resistance: it contains, by mass%, C: 0.03-0.12%, Si: 0.05-2.00%, Mn: 0.05-3.00%, P: 0.03% or less, S: 0.010% or less, Ni: 18.0% or more and less than 25.0%, Cr: 22.0% or more and less than 30.0%. .0%, Co: 0.04~0.80%, Ti: 0.002~0.010%, Nb: 0.1~1.0%, V: 0.01~1.00%, Al: 0.001% or more and less than 0.030%, N: 0.10~0.35%, Mo: 0~1.00%, W: 0~1.00%, B: 0~0.010%, and Ca: 0~0.0100%, and the balance is Fe and impurities.
[0041] Therefore, the present inventors have studied how to achieve both excellent creep strength and excellent stress relaxation cracking resistance in an austenitic stainless steel alloy material satisfying the above-mentioned chemical composition from the viewpoint of microstructure.
[0042] Usually, in the austenitic stainless steel alloy material for boiler use, fine precipitates such as Ti precipitates, Nb precipitates and V precipitates are generated during use in a high temperature environment, and the precipitation strengthening of these precipitates is used to improve the creep strength. Therefore, in the austenitic stainless steel alloy material disclosed in Patent Document 1 and Patent Document 2, heat treatment (solution treatment) is implemented in the final stage of the manufacturing process. Thus, the precipitates in the austenitic stainless steel alloy material are dissolved as much as possible, so that Ti, Nb, and V become a solid solution state. This is to use the austenitic stainless steel alloy material under a high temperature environment, and to use these solid solution elements to form fine precipitates to improve the creep strength.
[0043] However, the present inventors believe that by not reducing the precipitates in the austenitic stainless steel alloy material as much as possible in advance so that Ti, Nb and V are in a solid solution state as in the past, but intentionally making fine precipitates exist in the austenitic stainless steel alloy material in advance, it should be possible to improve not only the creep strength but also the stress relaxation cracking resistance.
[0044] The pinning effect of fine precipitates pre-existing in the austenitic stainless steel alloy material can maintain the grains of the austenitic stainless steel alloy material finer. In this case, the grain boundary area in the alloy material increases. By increasing the grain boundary area, the stress relaxation crack resistance can be improved.
[0045] On the other hand, when precipitates are pre-existing in the austenitic stainless steel alloy material, it is difficult to generate new fine precipitates during use in a high temperature environment. Moreover, it is also conceivable that the existing precipitates will coarsen during use in a high temperature environment. In this case, sufficient creep strength may not be obtained. However, the research results of the present inventors have found that in the austenitic stainless steel alloy material having the above chemical composition before being used for boiler purposes, if there are 5000 precipitates with a circle equivalent diameter of 0.5 to 2.0 μm / mm 2 As described above, even when used in a high temperature environment, sufficient creep strength can be obtained.
[0046] Based on the above findings, the present inventors have found that, unlike the conventional austenitic stainless steel alloy materials described in Patent Documents 1 and 2, by reducing the precipitates in the alloy material as much as possible to improve the creep strength under high temperature environments, the present inventors have found that, instead of reducing the precipitates in the alloy material as much as possible to improve the creep strength under high temperature environments, the present inventors have found that, in the austenitic stainless steel alloy material, the creep strength under high temperature environments can be improved by intentionally making the precipitates to be 5000 / mm 2 As described above, it is possible to achieve both excellent creep strength and excellent stress relaxation cracking resistance, thereby completing the austenitic stainless steel alloy material of the present embodiment.
[0047] The austenitic stainless steel alloy material of the present embodiment completed based on the above technical concept has the following configuration.
[0048] [1] An austenitic stainless steel alloy material comprising, by mass%,
[0049] C: 0.03~0.12%,
[0050] Si: 0.05-2.00%,
[0051] Mn: 0.05-3.00%,
[0052] P: 0.03% or less,
[0053] S: 0.010% or less,
[0054] Ni: 18.0% or more and less than 25.0%,
[0055] Cr: 22.0% or more and less than 30.0%,
[0056] Co: 0.04-0.80%,
[0057] Ti: 0.002~0.010%,
[0058] Nb: 0.1-1.0%,
[0059] V: 0.01~1.00%,
[0060] Al: 0.001% or more and less than 0.030%,
[0061] N: 0.10~0.35%,
[0062] Mo: 0-1.00%,
[0063] W: 0~1.00%,
[0064] B: 0~0.010%, and
[0065] Ca: 0 to 0.0100%, and
[0066] The balance is Fe and impurities.
[0067] The number density of precipitates with a circle equivalent diameter of 0.5 to 2.0 μm in the austenitic stainless steel alloy material is 5000 / mm 2 above.
[0068] [2] The austenitic stainless steel alloy material according to [1], comprising a
[0069] Mo: 0.01~1.00%,
[0070] W: 0.01~1.00%,
[0071] B: 0.001~0.010%, and
[0072] Ca: One or more elements selected from the group consisting of 0.0001 to 0.0100%.
[0073] Hereinafter, the austenitic stainless steel alloy material according to the present embodiment will be described in detail.
[0074] [Characteristics of the alloy material of this embodiment]
[0075] The austenitic stainless steel alloy material of the present embodiment satisfies the following feature 1 and feature 2.
[0076] (Feature 1)
[0077] The chemical composition contains, by mass%, C: 0.03-0.12%, Si: 0.05-2.00%, Mn: 0.05-3.00%, P: 0.03% or less, S: 0.010% or less, Ni: 18.0% or more and less than 25.0%, Cr: 22.0% or more and less than 30.0%, Co: 0.04-0.80%, Ti: 0.002-0.010%, Nb: 0.1-1.0%, V: 0.01-1.00%, Al: 0.001% or more and less than 0.030%, N: 0.10-0.35%, Mo: 0-1.00%, W: 0-1.00%, B: 0-0.010%, and Ca: 0-0.0100%, and the balance is Fe and impurities.
[0078] (Feature 2)
[0079] The number density of precipitates with a circle equivalent diameter of 0.5 to 2.0 μm is 5000 / mm 2 above.
[0080] Hereinafter, feature 1 and feature 2 will be described.
[0081] [About (Feature 1) Chemical composition]
[0082] [About Essential Elements]
[0083] The chemical composition of the austenitic stainless steel alloy material of the present embodiment contains the following elements.
[0084] C: 0.03~0.12%
[0085] Carbon (C) improves the creep strength of the alloy material in a high temperature environment. If the C content is less than 0.03%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0086] On the other hand, if the C content exceeds 0.12%, even if the contents of other elements are within the range of this embodiment, M is generated at the grain boundaries. 23 C6 type Cr carbide. In this case, a Cr-poor region is generated at the grain boundary. Therefore, the stress relaxation cracking resistance of the alloy material is reduced.
[0087] Therefore, the C content is 0.03 to 0.12%.
[0088] The lower limit of the C content is preferably more than 0.03%, more preferably 0.04%, and even more preferably 0.05%.
[0089] The upper limit of the C content is preferably 0.11%, more preferably 0.10%, and further preferably 0.09%.
[0090] Si: 0.05~2.00%
[0091] Silicon (Si) deoxidizes the alloy in the steelmaking process. Si also improves the oxidation resistance of the alloy material in a high temperature environment. If the Si content is less than 0.05%, the above effects cannot be fully obtained even if the contents of other elements are within the range of this embodiment.
[0092] On the other hand, when the Si content exceeds 2.00%, the welding hot cracking resistance decreases even if the contents of other elements are within the ranges of the present embodiment.
[0093] Therefore, the Si content is 0.05 to 2.00%.
[0094] The lower limit of the Si content is preferably 0.10%, more preferably 0.15%, further preferably 0.18%, further preferably 0.20%.
[0095] The upper limit of the Si content is preferably 1.80%, more preferably 1.60%, more preferably 1.40%, more preferably 1.30%, and still more preferably 1.25%.
[0096] Mn: 0.05~3.00%
[0097] Manganese (Mn) deoxidizes the welded portion of the alloy material during welding. Mn also stabilizes austenite. If Mn is less than 0.05%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0098] On the other hand, if the Mn content exceeds 3.00%, even if the contents of other elements are within the range of this embodiment, a sigma phase is likely to be generated when used in a high temperature environment. The σ phase reduces the toughness and creep ductility of the alloy material in a high temperature environment.
[0099] Therefore, the Mn content is 0.05 to 3.00%.
[0100] The lower limit of the Mn content is preferably 0.10%, more preferably 0.15%, more preferably 0.20%, more preferably 0.30%, more preferably 0.40%, and still more preferably 0.45%.
[0101] The preferred upper limit of the Mn content is less than 3.00%, more preferably 2.99%, more preferably 2.95%, more preferably 2.90%, more preferably 2.80%, more preferably 2.60%, more preferably 2.40%, more preferably 2.35%, more preferably 2.20%, and more preferably 2.00%.
[0102] P: 0.03% or less
[0103] Phosphorus (P) is inevitably contained. That is, the P content exceeds 0%.
[0104] P segregates at the grain boundaries of the alloy material. If the P content exceeds 0.03%, even if the contents of other elements are within the range of the present embodiment, the above segregation occurs, and the stress relaxation cracking resistance decreases.
[0105] Therefore, the P content is 0.03% or less.
[0106] The P content is preferably as low as possible. However, excessive reduction of the P content will increase the production cost of the alloy material. Therefore, considering normal industrial production, the preferred lower limit of the P content is 0.01%.
[0107] The preferred upper limit of the P content is 0.02%.
[0108] S: 0.010% or less
[0109] Sulfur (S) is inevitably contained. That is, the S content exceeds 0%.
[0110] S segregates at the grain boundaries of the alloy material. If the S content exceeds 0.010%, the above segregation occurs even if the contents of other elements are within the range of the present embodiment, and the stress relaxation cracking resistance decreases.
[0111] Therefore, the S content is set to 0.010% or less.
[0112] The S content is preferably as low as possible. However, excessive reduction of the S content will increase the production cost of the alloy material. Therefore, considering normal industrial production, the preferred lower limit of the S content is 0.001%.
[0113] The upper limit of the S content is preferably 0.008%, more preferably 0.006%, further preferably 0.004%, further preferably 0.003%.
[0114] Ni: 18.0% or more and less than 25.0%
[0115] Nickel (Ni) stabilizes austenite and improves the creep strength of the alloy material in a high temperature environment. If the Ni content is less than 18.0%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment.
[0116] On the other hand, when the Ni content is 25.0% or more, the above-mentioned effect is saturated and the manufacturing cost increases.
[0117] Therefore, the Ni content is 18.0% or more and less than 25.0%.
[0118] The lower limit of the Ni content is preferably 18.4%, more preferably 18.8%, more preferably 19.2%, and further preferably 19.5%.
[0119] The upper limit of the Ni content is preferably 24.9%, more preferably 24.8%, more preferably 24.4%, more preferably 24.0%, and still more preferably 23.6%.
[0120] Cr: 22.0% or more and less than 30.0%
[0121] Chromium (Cr) improves the corrosion resistance of the alloy material in a high temperature environment. If the Cr content is less than 22.0%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0122] On the other hand, when the Cr content is 30.0% or more, even if the contents of other elements are within the range of the present embodiment, the stability of austenite decreases in a high temperature environment. In this case, the creep strength of the alloy material decreases.
[0123] Therefore, the Cr content is 22.0% or more and less than 30.0%.
[0124] The lower limit of the Cr content is preferably 22.5%, more preferably 23.0%, and further preferably 23.5%.
[0125] The upper limit of the Cr content is preferably 29.9%, more preferably 29.8%, more preferably 29.5%, more preferably 29.0%, more preferably 28.5%, more preferably 28.0%, more preferably 27.5%, and more preferably 27.0%.
[0126] Co: 0.04~0.80%
[0127] Cobalt (Co) stabilizes austenite and improves the creep strength of the alloy material in a high temperature environment. If the Co content is less than 0.04%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0128] On the other hand, when the Co content exceeds 0.80%, the raw material cost becomes high.
[0129] Therefore, the Co content is 0.04 to 0.80%.
[0130] The lower limit of the Co content is preferably 0.05%, more preferably 0.06%, and further preferably 0.08%.
[0131] The upper limit of the Co content is preferably 0.70%, more preferably 0.60%, further preferably 0.55%, further preferably 0.50%.
[0132] Ti: 0.002~0.010%
[0133] Titanium (Ti) forms Ti precipitates to improve the creep strength of the alloy material in a high temperature environment. Ti also improves the stress relaxation cracking resistance of the alloy material by forming Ti precipitates. If the Ti content is less than 0.002%, even if the contents of other elements are within the range of this embodiment, the above effects cannot be fully obtained.
[0134] On the other hand, if the Ti content exceeds 0.010%, even if the contents of other elements are within the range of the present embodiment, coarse Ti precipitates are generated. In this case, the weld heat crack resistance of the weld heat affected zone formed in the alloy material during welding is reduced.
[0135] Therefore, the Ti content is 0.002 to 0.010%.
[0136] The lower limit of the Ti content is preferably 0.003%, more preferably 0.004%.
[0137] The upper limit of the Ti content is preferably 0.009%, more preferably 0.008%.
[0138] Nb: 0.1~1.0%
[0139] Niobium (Nb) forms Nb precipitates to improve the creep strength of the alloy material in a high temperature environment. Nb also improves the stress relaxation cracking resistance of the alloy material by forming Nb precipitates. If the Nb content is less than 0.1%, even if the contents of other elements are within the range of this embodiment, the above effects cannot be fully obtained.
[0140] On the other hand, if the Nb content exceeds 1.0%, even if the contents of other elements are within the ranges of the present embodiment, the resistance to hot cracking of the alloy material is reduced at the heat affected zone of the alloy material during welding of the alloy material.
[0141] Therefore, the Nb content is 0.1 to 1.0%.
[0142] The lower limit of the Nb content is preferably 0.2%, more preferably 0.3%, and further preferably 0.4%.
[0143] The upper limit of the Nb content is preferably 0.9%, more preferably 0.8%, and further preferably 0.7%.
[0144] V: 0.01~1.00%
[0145] Vanadium (V) forms V precipitates to improve the creep strength of the alloy material in a high temperature environment. V also improves the stress relaxation cracking resistance of the alloy material by forming V precipitates. If the V content is less than 0.01%, even if the contents of other elements are within the range of this embodiment, the above effects cannot be fully obtained.
[0146] On the other hand, if the V content exceeds 1.00%, even if the contents of other elements are within the ranges of the present embodiment, the resistance to welding hot cracking is reduced at the weld heat affected zone of the alloy material during welding of the alloy material.
[0147] Therefore, the V content is 0.01 to 1.00%.
[0148] The lower limit of the V content is preferably 0.02%, more preferably 0.03%, and further preferably 0.04%.
[0149] The upper limit of the V content is preferably 0.80%, more preferably 0.75%, more preferably 0.70%, more preferably 0.65%, more preferably 0.60%, more preferably 0.40%, more preferably 0.35%, and more preferably 0.25%.
[0150] Al: 0.001% or more and less than 0.030%
[0151] Aluminum (Al) deoxidizes the alloy in the steelmaking process. Al also improves the oxidation resistance of the alloy material in a high temperature environment. If the Al content is less than 0.001%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment.
[0152] On the other hand, when the Al content is 0.030% or more, the hot workability of the alloy material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0153] Therefore, the Al content is 0.001% or more and less than 0.030%.
[0154] The lower limit of the Al content is preferably 0.002%, more preferably 0.003%, and further preferably 0.005%.
[0155] The upper limit of the Al content is preferably 0.029%, more preferably 0.028%, more preferably 0.027%, more preferably 0.026%, and still more preferably 0.025%.
[0156] In addition, the Al content is the content (mass %) of acid-soluble Al (sol. Al).
[0157] N: 0.10~0.35%
[0158] Nitrogen (N) is dissolved in the matrix (parent phase) to stabilize austenite. The dissolved N also forms fine nitrides in the alloy material during use in a high temperature environment. The fine nitrides strengthen the Cr-poor region. Therefore, the stress relaxation crack resistance of the alloy material becomes higher. The fine nitrides generated during use in a high temperature environment also improve the creep strength of the alloy material by precipitation strengthening. If the N content is less than 0.10%, even if the content of other elements is within the range of this embodiment, the above-mentioned effect cannot be fully obtained.
[0159] On the other hand, when the N content exceeds 0.35%, even if the contents of other elements are within the range of the present embodiment, coarse nitrides are generated. Coarse nitrides reduce the toughness of the alloy material.
[0160] Therefore, the N content is 0.10 to 0.35%.
[0161] The lower limit of the N content is preferably 0.11%, more preferably 0.12%, further preferably 0.14%, further preferably 0.16%.
[0162] The upper limit of the N content is preferably 0.33%, more preferably 0.31%, and further preferably 0.29%.
[0163] The balance of the chemical composition of the austenitic stainless steel alloy material of the present embodiment is Fe and impurities. Here, impurities refer to substances mixed from ore, waste materials or manufacturing environment as raw materials during industrial production of austenitic stainless steel alloy materials, which are not intentionally contained and are allowed within the range that does not adversely affect the austenitic stainless steel alloy material of the present embodiment.
[0164] [About Optional Elements]
[0165] The chemical composition of the austenitic stainless steel alloy material of the present embodiment may further contain
[0166] Mo: 0-1.00%,
[0167] W: 0~1.00%,
[0168] B: 0~0.010%, and
[0169] Ca: One or more elements selected from the group consisting of 0 to 0.0100% replace a portion of Fe.
[0170] These elements are all optional elements and may not be contained. These optional elements are described below.
[0171] [About (Group 1) Mo and W]
[0172] The chemical composition of the austenitic stainless steel alloy material of the present embodiment may further contain one or more elements selected from the group consisting of Mo and W in place of a portion of Fe. These elements are arbitrary elements and all increase the creep strength of the austenitic stainless steel alloy material.
[0173] Mo: 0~1.00%
[0174] Molybdenum (Mo) is an arbitrary element and may not be contained. That is, the Mo content may be 0%.
[0175] When Mo is contained, that is, when the Mo content exceeds 0%, Mo improves the creep strength of the alloy material by solid solution strengthening during use in a high temperature environment. The above effect can be obtained to some extent as long as Mo is contained in a small amount.
[0176] However, if the Mo content exceeds 1.00%, even if the contents of other elements are within the range of this embodiment, intermetallic compounds such as LAVES phases will be generated in the grains. In this case, secondary induced precipitation hardening increases, and the strength difference between the grains and the grain boundaries increases. Therefore, the stress relaxation cracking resistance decreases.
[0177] Therefore, the Mo content is 0 to 1.00%, and when contained, the Mo content is 1.00% or less.
[0178] The lower limit of the Mo content is preferably more than 0%, more preferably 0.01%, more preferably 0.03%, more preferably 0.05%, and still more preferably 0.08%.
[0179] The upper limit of the Mo content is preferably 0.90%, more preferably 0.85%, more preferably 0.80%, more preferably 0.70%, more preferably 0.60%, more preferably 0.50%, more preferably 0.40%, and more preferably 0.30%.
[0180] W: 0~1.00%
[0181] Tungsten (W) is an arbitrary element and may not be contained. That is, the W content may be 0%.
[0182] When W is contained, that is, when the W content exceeds 0%, W improves the creep strength of the alloy material by solid solution strengthening during use of the alloy material in a high temperature environment. The above effect can be obtained to some extent as long as W is contained in a small amount.
[0183] However, if the W content exceeds 1.00%, even if the contents of other elements are within the range of this embodiment, intermetallic compounds such as LAVES phases will be generated in the grains. In this case, secondary induced precipitation hardening increases, and the strength difference between the grains and the grain boundaries increases. Therefore, the stress relaxation cracking resistance decreases.
[0184] Therefore, the W content is 0 to 1.00%, and when contained, the W content is 1.00% or less.
[0185] The preferred lower limit of the W content is more than 0%, more preferably 0.01%, more preferably 0.03%, more preferably 0.05%, and still more preferably 0.10%.
[0186] The upper limit of the W content is preferably 0.90%, more preferably 0.80%, more preferably 0.70%, more preferably 0.60%, more preferably 0.50%, more preferably 0.40%, more preferably 0.35%, and more preferably 0.30%.
[0187] [About (Group 2) B]
[0188] The austenitic stainless steel alloy material of the present embodiment may further contain B.
[0189] B: 0~0.010%
[0190] Boron (B) is an arbitrary element and may not be contained. That is, the B content may be 0%.
[0191] When B is contained, that is, when the B content exceeds 0%, B segregates at the grain boundaries in a high temperature environment and increases the grain boundary strength. Therefore, the stress relaxation cracking resistance of the alloy material becomes higher. The above effect can be obtained to some extent as long as B is contained in a small amount.
[0192] However, if the B content exceeds 0.010%, even if the contents of other elements are within the ranges of the present embodiment, B promotes the formation of Cr carbides at the grain boundaries. In this case, the stress relaxation cracking resistance of the alloy material decreases.
[0193] Therefore, the B content is 0 to 0.010%, and when contained, the B content is 0.010% or less.
[0194] The lower limit of the B content is preferably more than 0%, more preferably 0.001%, and even more preferably 0.002%.
[0195] The upper limit of the B content is preferably 0.009%, more preferably 0.008%, further preferably 0.007%, further preferably 0.006%.
[0196] [About (Group 3) Ca]
[0197] The austenitic stainless steel alloy material according to the present embodiment may further contain Ca.
[0198] Ca: 0~0.0100%
[0199] Calcium (Ca) is an arbitrary element and may not be contained. That is, the Ca content may be 0%.
[0200] When Ca is contained, that is, when the Ca content exceeds 0%, Ca fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the hot workability of the alloy material. The above-mentioned effect can be obtained to some extent as long as Ca is contained in a small amount.
[0201] However, when the Ca content exceeds 0.0100%, even if the contents of other elements are within the ranges of the present embodiment, the purity of the alloy material decreases and the hot workability of the alloy material decreases.
[0202] Therefore, the Ca content is 0 to 0.0100%, and when contained, the Ca content is 0.0100% or less.
[0203] The preferred lower limit of the Ca content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, more preferably 0.0005%, more preferably 0.0008%, and still more preferably 0.0010%.
[0204] The upper limit of the Ca content is preferably 0.0090%, more preferably 0.0080%, more preferably 0.0070%, more preferably 0.0060%, more preferably 0.0050%, and still more preferably 0.0045%.
[0205] [Regarding (Feature 2) Number Density ND (Number Density) of Fine Precipitates]
[0206] In the austenitic stainless steel alloy material of the present embodiment, the number density ND of precipitates having an equivalent circle diameter of 0.5 to 2.0 μm is also 5000 pcs / mm 2 above.
[0207] As described above, in the conventional austenitic stainless steel alloy material, the precipitates in the alloy material are reduced as much as possible by performing a solid solution treatment. However, in the austenitic stainless steel alloy material of the present embodiment, by actively allowing precipitates of a specific size to exist in the alloy material, both excellent creep strength and excellent stress relaxation crack resistance are achieved.
[0208] Here, precipitates with an equivalent circle diameter of 0.5 to 2.0 μm are defined as "fine precipitates". Fine precipitates maintain the grains of austenitic stainless steel alloy materials finer through the pinning effect. As a result, the grain boundary area of the austenitic stainless steel alloy material increases, and the stress relaxation crack resistance increases. In addition, fine precipitates with an equivalent circle diameter of 0.5 to 2.0 μm exhibit precipitation strengthening function during use in high temperature environments, thereby improving the creep strength of austenitic stainless steel alloy materials.
[0209] In an austenitic stainless steel alloy material satisfying characteristic 1, if the number density ND of fine precipitates is 5000 pieces / mm 2 The above can achieve both excellent creep strength and excellent stress relaxation crack resistance.
[0210] The preferred lower limit of the number density ND of fine precipitates is 5200 pieces / mm 2 , more preferably 5500 pieces / mm 2 , more preferably 6000 pieces / mm 2 , more preferably 6200 pcs / mm 2 .
[0211] The upper limit of the number density ND of fine precipitates is not particularly limited. When the austenitic stainless steel alloy material satisfies the feature 1, the upper limit of the number density ND of fine precipitates is, for example, 20,000 precipitates / mm 2 , for example, 18000 pieces / mm 2 , for example, 15000 pieces / mm 2 .
[0212] [Method for measuring the number density ND of fine precipitates]
[0213] The number density ND of fine precipitates can be obtained by the following method.
[0214] First, a test piece is collected from an austenitic stainless steel alloy material. When the austenitic stainless steel alloy material is an alloy tube, a test piece including the central portion of the wall thickness is collected. The surface of the test piece that is perpendicular to the tube axis direction of the alloy tube and includes the central portion of the wall thickness is used as the observation surface, and the central portion of the wall thickness is used as the observation field.
[0215] When the austenitic stainless steel alloy material is an alloy plate, a test piece including the center of the plate thickness is collected. The surface of the test piece that is perpendicular to the rolling direction of the alloy plate and includes the center of the plate thickness is used as the observation surface, and the center of the plate thickness is used as the observation field.
[0216] When the austenitic stainless steel alloy material is a bar, a test piece including the R / 2 portion is collected. Here, R refers to the radius of the cross section perpendicular to the axial direction of the bar. The R / 2 portion refers to the central part of the radius in the above cross section. The cross section perpendicular to the longitudinal direction of the bar and the surface including the R / 2 portion on the surface of the test piece is used as the observation surface, and the R / 2 portion is set as the observation field.
[0217] After the observation surface was mirror-polished, an optical microscope was used to obtain a microstructure photograph of the observation field in the observation surface after the mirror-polishing at a magnification of 500. The area of the observation field was set to 140 μm×160 μm.
[0218] Using microstructure photographs obtained by optical microscope observation, the equivalent circular diameter of the particles in the observation field is calculated. Here, the equivalent circular diameter refers to the diameter of a circle with the same area as the area of the particle. The equivalent circular diameter can be calculated by known image processing. The particles in the field observation can be easily identified by contrast. Particles with an equivalent circular diameter of 0.5 to 2.0 μm are identified as precipitates (fine precipitates). Based on the number of all fine precipitates in the observation field and the area of the observation field, the number density of fine precipitates (pieces / mm 2 ). In addition, the fine precipitates are, for example, any one or more of Ti precipitates containing Ti, Nb precipitates containing Nb, and V precipitates containing V.
[0219] [Effects of Austenitic Stainless Steel Alloy Materials]
[0220] The austenitic stainless steel alloy material of the present embodiment satisfies the feature 1 and the feature 2. As a result, the austenitic stainless steel alloy material of the present embodiment can achieve both excellent creep strength and excellent stress relaxation cracking resistance.
[0221] [Microstructure of Austenitic Stainless Steel Alloy Materials]
[0222] The microstructure of the alloy material of the present embodiment is formed of austenite.
[0223] [Shape of Austenitic Stainless Steel Alloy Materials]
[0224] The shape of the austenitic stainless steel alloy material of the present embodiment is not particularly limited. The austenitic stainless steel alloy material may be an alloy tube or an alloy plate. The austenitic stainless steel alloy material may be a bar. The austenitic stainless steel alloy material of the present embodiment is preferably an alloy tube.
[0225] [Method for producing austenitic stainless steel alloy material]
[0226] A method for producing the austenitic stainless steel alloy material according to the present embodiment will be described.
[0227] The manufacturing method described later is an example of the manufacturing method of the austenitic stainless steel alloy material of the present embodiment. Therefore, the austenitic stainless steel alloy material of the present embodiment can also be manufactured by other manufacturing methods other than the manufacturing method described later. However, the manufacturing method described later is a preferred example of the manufacturing method of the austenitic stainless steel alloy material of the present embodiment.
[0228] The method for producing the alloy material according to the present embodiment includes the following steps.
[0229] (Process 1) Preparation process
[0230] (Process 2) Hot working process
[0231] (Process 3) High temperature maintenance process
[0232] (Process 4) Cold working process
[0233] (Step 5) Precipitation Heat Treatment Step
[0234] In the above-mentioned manufacturing process, when the holding temperature in the high-temperature holding process is defined as T1 (°C), the holding time at the holding temperature T1 is defined as t1 (minutes), the heat treatment temperature in the precipitation heat treatment process is defined as T2 (°C), and the holding time at the heat treatment temperature T2 is defined as t2 (minutes), the following formulas (A) to (C) are satisfied.
[0235] (1 / 20)×{(T1-700) 2 +t1} / (5Nb+30Ti+5V)≥4100(A)
[0236] T1≥T2(B)
[0237] (T2+t2)×(Nb+50Ti+20V)≥1000(C)
[0238] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (A) and formula (C).
[0239] Hereinafter, each step will be described.
[0240] [(Process 1) Preparation process]
[0241] In the preparation step, a billet having a chemical composition satisfying the above-mentioned feature 1 is prepared. The billet may be supplied by a third party or may be manufactured. The billet may be an ingot, a slab, a bloom, or a billet.
[0242] When manufacturing the billet, the billet is manufactured by the following method. A molten alloy having a chemical composition satisfying the above-mentioned feature 1 is manufactured. A steel ingot is manufactured by an ingot casting method using the manufactured molten alloy. A slab, bloom or billet can also be manufactured by a continuous casting method using the manufactured molten alloy. The manufactured ingot, slab or bloom can also be subjected to hot working to manufacture a billet. For example, a steel ingot can also be subjected to hot forging to manufacture a cylindrical billet, which is used as a billet. In this case, there is no particular limitation on the temperature of the billet immediately before hot forging begins, and it is, for example, 1100 to 1300°C. There is no particular limitation on the method for cooling the billet after hot forging.
[0243] [(Process 2) Hot working process]
[0244] In the hot working step, the blank prepared in the preparation step is hot worked to produce an intermediate alloy material. The intermediate alloy material may be, for example, an alloy tube, an alloy plate, or an alloy rod.
[0245] When the intermediate alloy material is an alloy tube, the following processing is performed in the hot working process. First, a cylindrical billet is prepared. A through hole is formed along the central axis of the cylindrical billet by mechanical processing. The cylindrical billet with the through hole is heated. The heated cylindrical billet is subjected to hot extrusion represented by a glass lubricant high-speed extrusion method to manufacture an intermediate alloy material (alloy tube). A hot stamping tube forming method can also be implemented instead of a hot extrusion method. There is no particular limitation on the heating temperature, for example, 1100 to 1300°C.
[0246] In addition, the alloy tube can also be manufactured by piercing and rolling by the Mannesmann method instead of hot extrusion. In this case, the cylindrical billet is heated. The heating temperature is not particularly limited, for example, 1100 to 1300°C. The heated cylindrical billet is pierced and rolled by a piercer to obtain a hollow tube. Furthermore, the hollow tube is stretched or sized by a mandrel mill, a reducing mill, a sizing mill, etc. to manufacture an intermediate alloy material (alloy tube).
[0247] When the intermediate alloy material is an alloy plate, the hot working process uses one or more rolling mills equipped with a pair of work rolls. In this case, a billet such as a slab is heated. The heating temperature is not particularly limited, for example, 1100 to 1300° C. The heated billet is hot rolled using a rolling mill to produce an intermediate alloy material (alloy plate).
[0248] When the intermediate alloy material is an alloy bar, the hot working process uses, for example, a blooming mill and / or a tandem mill composed of a plurality of rolling mills arranged in a row. In this case, the billet is heated. The heating temperature is not particularly limited, and is, for example, 1100 to 1300° C. The heated billet is hot rolled using a blooming mill and / or a tandem mill to produce an intermediate alloy material (alloy bar).
[0249] [(Step 3) High temperature holding step]
[0250] In the high temperature holding step, the intermediate alloy material produced by the hot working step is held at a high temperature to fully dissolve the precipitates in the intermediate alloy material. The holding temperature T1 (° C.) and the holding time t1 (minutes) at the holding temperature T1 in the high temperature holding step are adjusted to the ranges shown below.
[0251] Maintaining temperature T1: 1100~1350℃
[0252] Holding time t1: 2 to 40 minutes
[0253] In the high temperature holding process, the intermediate alloy material cooled to room temperature in the hot working process may be heated to a holding temperature T1, and the temperature T1 may be maintained for a holding time t1. In addition, the intermediate alloy material just after the hot working process (i.e., the intermediate alloy material not cooled to room temperature) may be maintained at the temperature T1 for a holding time t1. After the holding time t1, the intermediate alloy material is rapidly cooled. The rapid cooling may be water cooling or oil cooling.
[0254] [(Process 4) Cold working process]
[0255] In the cold working process, after the intermediate alloy material is subjected to pickling treatment, cold working is performed. When the intermediate alloy material is an alloy tube or an alloy bar, the cold working is, for example, cold drawing. When the intermediate alloy material is an alloy plate, the cold working is, for example, cold rolling. By performing the cold working process, the grains can be refined based on recrystallization in the precipitation heat treatment process of the next process. The necking rate in the cold working process is not particularly limited, and is, for example, 10 to 90%.
[0256] [(Step 5) Precipitation Heat Treatment Step]
[0257] In the precipitation heat treatment step, the intermediate alloy material after the cold working step is heat treated to generate fine precipitates in the intermediate alloy material. The heat treatment temperature T2 (° C.) and the holding time t2 (minutes) at the heat treatment temperature T2 in the precipitation heat treatment step are adjusted to the following ranges.
[0258] Heat treatment temperature T2: 1000~1350℃
[0259] Holding time t2: 1 to 30 minutes
[0260] The intermediate alloy material is rapidly cooled after the holding time t2. The rapid cooling method may be water cooling or oil cooling.
[0261] [About Formula (A) to Formula (C)]
[0262] In the above-mentioned manufacturing process, the holding temperature T1 (°C), holding time t1 (minutes), heat treatment temperature T2 (°C) and holding time t2 (minutes) in the high-temperature holding process and the precipitation heat treatment process also satisfy equations (A) to (C).
[0263] (1 / 20)×{(T1-700) 2 +t1} / (5Nb+30Ti+5V)≥4100(A)
[0264] T1≥T2(B)
[0265] (T2+t2)×(Nb+50Ti+20V)≥1000(C)
[0266] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (A) and formula (C).
[0267] [About formula (A)]
[0268] Defined as F1 = (1 / 20) × {(T1-700) 2 +t1} / (5Nb+30Ti+5V). F1 is a conditional formula for fully dissolving the precipitates (Nb precipitates, Ti precipitates, V precipitates, etc.) in the intermediate alloy material during the high temperature holding process. In the austenitic stainless steel alloy material of the present embodiment, the N content is relatively high and is 0.10-0.35%. In the case where the N content is relatively high like this, in order to fully dissolve the Ti precipitates, a heat corresponding to the Ti content in the alloy material is required. Similarly, for Nb precipitates and V precipitates, in order to fully dissolve these precipitates, a heat corresponding to the Nb content and the V content of the alloy material is required.
[0269] In F1, the Nb content, the Ti content, and the V content are arranged in the denominator. That is, F1 is adjusted according to the Nb content, the Ti content, and the V content in the alloy material. As described above, in the austenitic stainless steel alloy material of the present embodiment, the N content is relatively high. Therefore, among the Nb precipitates, the Ti precipitates, and the V precipitates, the Ti having a strong bond with N is the least soluble. Therefore, the coefficient of Ti in F1 is relatively large.
[0270] If F1 is 4100 or more, sufficient heat is applied to the intermediate alloy material in the high-temperature holding step to dissolve the Nb precipitates, Ti precipitates, and V precipitates in the intermediate alloy material. Therefore, the precipitates in the intermediate alloy material can be sufficiently dissolved.
[0271] The preferred lower limit of F1 is 4200, and more preferably 4300.
[0272] [About formula (B)]
[0273] In the above manufacturing process, after the precipitates in the intermediate alloy material are substantially dissolved in the high temperature holding process, fine precipitates are generated in the intermediate alloy material in the precipitation heat treatment process. If the heat treatment temperature T2 is higher than the holding temperature T1, fine precipitates will not be fully generated in the intermediate alloy material in the precipitation heat treatment process. Therefore, the holding temperature T1 is set to be above the heat treatment temperature T2.
[0274] [About formula (C)]
[0275] In the precipitation heat treatment step, fine precipitates with a circle equivalent diameter of 0.5 to 2.0 μm are generated relative to the intermediate alloy material in which the precipitates are fully dissolved by the high temperature holding step. In order to make the number density ND of the fine precipitates 5000 pieces / mm 2 As described above, it is necessary to apply heat corresponding to the Nb content, the Ti content, and the V content in the intermediate alloy material to the intermediate alloy material.
[0276] It is defined as F2 = (T2 + t2) × (Nb + 50Ti + 20V). F2 is used to make the number density ND of fine precipitates 5000 pieces / mm 2 If F2 is 1000 or more, the number density of fine precipitates becomes 5000 pieces / mm2, provided that equations (A) and (B) are satisfied. 2 above.
[0277] The lower limit of F2 is preferably 1020, more preferably 1100, and further preferably 1200.
[0278] Through the above manufacturing process, an austenitic stainless steel alloy material satisfying characteristics 1 and 2 can be manufactured. In addition, the manufacturing method of the austenitic stainless steel alloy material of the present embodiment is not limited to the above manufacturing method. If an austenitic stainless steel alloy material satisfying characteristics 1 and 2 can be manufactured, it can also be manufactured by other manufacturing methods.
[0279] Example
[0280] The effects of the austenitic stainless steel alloy material of the present embodiment are further specifically described below by way of examples. The conditions in the following examples are one conditional example adopted to confirm the feasibility and effects of the austenitic stainless steel alloy material of the present embodiment. Therefore, the austenitic stainless steel alloy material of the present embodiment is not limited to this one conditional example.
[0281] [Manufacturing of alloy materials]
[0282] Steel ingots having the chemical compositions shown in Table 1-1 and Table 1-2 were produced.
[0283] [Table 1-1]
[0284] Table 1-1
[0285]
[0286] [Table 1-2]
[0287] Table 1-2
[0288]
[0289] The manufactured steel ingot was subjected to hot forging to manufacture a cylindrical billet with a diameter of 180 mm. The heating temperature of the steel ingot during hot forging was 1100 to 1300°C. The manufactured cylindrical billet was subjected to a hot working process. Specifically, the billet was heated in a heating furnace. The heating temperature in the hot working process was 1100 to 1300°C. The heated cylindrical billet was subjected to hot extrusion to manufacture a tube billet.
[0290] The produced blank tube was subjected to a high temperature holding step. Table 2 shows the holding temperature T1 (° C.) and holding time t1 (minutes) in the high temperature holding step.
[0291] [Table 2]
[0292] Table 2
[0293]
[0294] The blank tube after the high temperature holding step is subjected to cold working. Specifically, the blank tube is subjected to cold drawing. The necking ratio in the cold working is 20 to 70%.
[0295] The precipitation heat treatment process is performed on the tube blank after the cold working process. The heat treatment temperature T2 (°C) and the holding time t2 (minutes) at the heat treatment temperature T2 in the precipitation heat treatment process are shown in Table 2. In addition, the F1 value is shown in the "F1" column in Table 2. In the "T1 ≥ T2?" column, "T(Tru e :Correct)” means that the temperature T1 is kept above the heat treatment temperature T2, “F(Fals e: Error)" indicates that the holding temperature T1 is lower than the heat treatment temperature T2. The F2 value is shown in the "F2" column.
[0296] Through the above-mentioned manufacturing steps, an austenitic stainless steel alloy material (alloy pipe) is manufactured.
[0297] [Evaluation test]
[0298] The following evaluation tests were carried out using the produced alloy materials.
[0299] (Test 1) ND measurement test of number density of fine precipitates
[0300] (Test 2) Creep strength evaluation test
[0301] (Test 3) Stress relaxation crack resistance evaluation test
[0302] Hereinafter, each evaluation test will be described.
[0303] [(Test 1) ND measurement test of number density of fine precipitates]
[0304] For the austenitic stainless steel alloy material of each test number, the number density of fine precipitates (number / mm) was measured by the method described in [Method for measuring the number density ND of fine precipitates]. 2 The number density ND of the obtained fine precipitates is shown in "Number density ND (pieces / mm 2 )" column.
[0305] [(Test 2) Creep strength evaluation test]
[0306] The following creep strength evaluation test was performed on the alloy material (alloy tube) of each test number.
[0307] A creep rupture test piece based on JIS Z2271:2010 was collected from the center of the wall thickness of the alloy material (alloy tube) of each test number. The cross section of the parallel part of the creep rupture test piece perpendicular to the axial direction is circular. The outer diameter of the parallel part is 6 mm and the length is 30 mm. The length direction of the creep rupture test piece is parallel to the tube axis direction of the alloy tube.
[0308] The collected creep rupture test pieces were used to perform a creep rupture test in accordance with JIS Z2271: 2010. Specifically, the creep rupture test pieces were heated to 700° C. Thereafter, the creep rupture test was performed. The test stress was 80 MPa. In the test, the creep rupture time (hours) was determined.
[0309] Based on the obtained creep rupture time, the creep strength was evaluated as follows.
[0310] Evaluation E (Excellent): Creep rupture time is 1500 hours or more
[0311] Evaluation B (Bad): Creep rupture time is less than 1500 hours
[0312] In the case of evaluation E, it was judged that excellent creep strength was obtained. The evaluation results are shown in the "Creep Strength" column in Table 2.
[0313] [(Test 3) Stress relaxation crack resistance evaluation test]
[0314] The alloy material (alloy tube) of each test number was produced from the center of the wall thickness. Figure 1 The C-ring type restraint weld crack test piece shown in the figure is a test piece with an outer diameter OD = 6mm, an inner diameter ID = 4mm, and a length L = 20mm. The cross section of the test piece perpendicular to the pipe axis is a partially open ring. Figure 1 As shown in FIG. 1 , a gap G of 1.5 mm is formed at the opening. When the C-ring type restrained weld crack test piece is observed from the tube axis direction, a notch is formed at a position 180° from the opening relative to the central axis of the test piece. The width NW of the notch is set to 0.4 mm, the depth NOD is set to 0.5 mm, and the curvature radius R of the bottom is set to 0.2 mm.
[0315] like Figure 2 As shown, when the C-ring type restrained weld crack test piece is observed from the tube axis direction, the positions at 90° and 270° relative to the opening are restrained from both sides by external force P, so that the ends of the opening are butted against each other. Then, the outer peripheral surface sides of the butted parts are welded together by TIG (Tungsten Inert Gas) welding. More specifically, the entire length of the C-ring type restrained weld crack test piece in the tube axis direction is welded together by TIG welding. The restraint stress is generated in the cut portion by the joint welding. The conditions of TIG welding are the same in any test number.
[0316] The C-ring type restraint welding crack test piece after joint welding was subjected to a heat treatment at 650°C for 500 hours. After the heat treatment, the number of cracks generated at the cut bottom of the C-ring type restraint welding crack test piece was counted. Specifically, crack observation test pieces including the cut bottom of the C-ring type restraint welding crack test piece and a cross section perpendicular to the tube axis direction of the C-ring type restraint welding crack test piece were collected at 3 locations in the tube axis direction. The surface of each crack observation test piece corresponding to the above cross section was used as the observation surface. After the observation surface was mirror-polished, it was etched using a 10% oxalic acid aqueous solution. After etching, as shown in FIG. Figure 3As shown, in the observation plane, the number of grains contained in the cut bottom NB with a width NW is counted (in Figure 3 In the observation surface, the number of cracks propagating from the notch bottom NB was counted. The total number of crystal grains contained in the notch bottom NB of the three test pieces and the total number of cracks propagating from the notch bottom NB of the three test pieces were used to calculate the crack generation rate according to the following formula.
[0317] Crack generation rate = total number of cracks / total number of grains contained in the notch bottom NB × 100
[0318] According to the obtained crack generation rate, the stress relaxation crack resistance was evaluated as follows.
[0319] Evaluation E: Crack generation rate is 30% or less
[0320] Evaluation B: Crack generation rate exceeds 30%
[0321] In the case of evaluation E, it was determined that excellent stress relaxation cracking resistance was obtained. Table 2 shows the evaluation results.
[0322] [Test results]
[0323] Referring to Table 1-1, Table 1-2, and Table 2, in Test Nos. 1 to 12, the alloy material satisfies Characteristics 1 and 2. Therefore, sufficient creep strength is obtained in a high temperature environment, and excellent stress relaxation crack resistance is obtained.
[0324] On the other hand, in test numbers 13 and 14, F1 is too low and does not satisfy formula (A). Therefore, in the austenitic stainless steel alloy materials of these test numbers, the number density ND of fine precipitates is less than 5000 pieces / mm 2 As a result, sufficient stress relaxation crack resistance was not obtained.
[0325] In test numbers 15 to 17, the holding temperature T1 is lower than the heat treatment temperature T2, and the formula (B) is not satisfied. Therefore, in the austenitic stainless steel alloy materials of these test numbers, the number density ND of fine precipitates is less than 5000 pieces / mm 2 As a result, sufficient stress relaxation crack resistance was not obtained.
[0326] In test numbers 18 and 19, F2 is too low and does not satisfy formula (C). Therefore, in the austenitic stainless steel alloy materials of these test numbers, the number density ND of fine precipitates is less than 5000 pieces / mm 2 As a result, sufficient creep strength is not obtained. Also, sufficient stress relaxation crack resistance is not obtained.
[0327] The above describes the embodiments of the present invention. However, the above embodiments are merely examples for implementing the present invention. Therefore, the present invention is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented within the scope of the present invention.
Claims
1. An austenitic stainless steel alloy material, which contains, by mass%, C:0.03~0.12%、 Si: 0.05-2.00%, Mn: 0.05-3.00%, P: 0.03% or less, S: 0.010% or less, Ni: 18.0% or more and less than 25.0%, Cr: 22.0% or more and less than 30.0%, Co: 0.04-0.80%, Ti: 0.002~0.010%, Nb: 0.1-1.0%, V:0.01~1.00%、 Al: 0.001% or more and less than 0.030%, N:0.10~0.35%、 Mo: 0-1.00%, W:0~1.00%、 B: 0~0.010%, and Ca: 0 to 0.0100%, and The balance is Fe and impurities. The number density of precipitates with a circle equivalent diameter of 0.5 to 2.0 μm in the austenitic stainless steel alloy material is 5000 / mm 2 above.
2. The austenitic stainless steel alloy material according to claim 1, comprising Mo: 0.01~1.00%, W:0.01~1.00%、 B: 0.001~0.010%, and Ca: One or more elements selected from the group consisting of 0.0001 to 0.0100%.
Citation Information
Patent Citations
Austenitic stainless steel, and production method therefor
JP2004250783A
Austenitic stainless steel
WO2009044796A1